Granulocytic sarcoma presented as a reactivation of chronic myeloid leukemia after allogenic marrow transplantation - Oliveira, José Salvador Rodigues de (1998)
The authors report the case of a chronic myeloid leukemia (CML) patient submitted to allogenic bone marrow transplantation, who had probably never entered complete remission. The disease was reactivated as a granulocytic sarcoma, next to a platinum plate installed to correct a tibia fracture 11 years earlier. Its final event was a myeloid Ph1+ blastic crisis that was unsuccessfully treated with high doses of sc interferon and citarabine.